Elites Strategies of Political Manipulation: The Nigerian Case - Sufyan, Dahiru Tanko; Dauda, Mohammed (Kashere Journal of Politics and International Relations, 2025)
This paper explains the nexus between elites and political manipulation in the act of politicking. The study was expository in nature. It explored how the Nigerian elites employ various strategies that include linguistic strategy, character assassination, astroturfing and black boxing to manipulate the masses/ the political system for their interest. These strategies employed by the elites in the political space are usually perpetrated through the use of mass media/social media, campaigns, rallies, public speeches, government agencies and decision making process, among other medium to attract support for political gain. The choice of words and actions of political elites in Nigeria has exposed the fragile nature of the Nigerian political system. As such, the politics of hatred and bitterness does not only create enmity amongst the elites but also create tension, hatred and crisis amongst the masses. The implication is that, national unity and cohesion is being threatened.